La charte ou les apories de la concertation - Lionel Laslaz (VertigO)
This paper proposes an approach in three times. At first, a theoretical and spatialised reflection on social acceptance makes it possible to clarify the use of the term and to distinguish it in particular from acceptability. Social acceptance is the context in which the tensions of actors take place: it is developed from the moment the actors have defined and stated the conditions of acceptability. Mediocre, it explains the reluctance of some of them to enter into the so-called virtuous contractual processes. In a second part, the paper focuses on the results of the municipalities’ membership to the charters of the three French alpine national parks. By focusing more on the Vanoise National Park, a third moment allows to interpret the results of the votes of the municipal councils on this scoping document, 15 years of particularly heavy and long construction. In the end, the charter to gain the social acceptance of national parks born and raised in the opposition only revived the latter in the case of the Vanoise, while the Ecrins and the Mercantour managed in two steps to obtain membership. Analyzing the postures of local politicians and the arrangements under way to carry out this document around which negotiations (and forms of participation) are supposed to improve social acceptance, the article draws a scene of debates in which these actors arrange themselves with space and spatialize their compromises.